Carbon Taxes and Stranded Assets: Evidence from Washington State - Stefano Carattini; Suphi Sen (Center for Economic Studies and ifo Institute (CESifo), 2019)
The climate challenge requires ambitious climate policy. A sudden increase in carbon prices can lead to major shocks to the stock market. Some assets will lose part of their value, others all of it, and hence become “stranded”. If the markets are not ready to absorb the shock, a financial crisis could follow. How well investors anticipate, and thus how large these shocks may be, is an empirical question. We analyze stock market reactions to the rejection of two carbon tax initiatives by voters in Washington state. We build proper counterfactuals for Washington state firms and find that these modest policy proposals with limited jurisdiction caused substantial readjustments on the stock market, especially for carbon-intensive stocks. Our results reinforce concerns about “stranded assets” and the risk of financial contagion. Our policy implications support the inclusion of transition risks in macroprudential policymaking and carbon disclosure and climate stress tests as the main policy responses.
Keywords: G12; H23; H71; L50; Q58; 330; carbon pricing; financial returns; systemic risk; macroprudential policies; voting